Outcomes of the addition of oral administration of curcumin-phospholipid to hyaluronic acid-based tear substitute for the treatment of dry eye disease - Borselli, Massimiliano; Ferrari, Fausto F.; Bianchi, Pietro; Rossi, Costanza; Scalzo, Giovanna Carnovale; Mangialavori, Domenica; Scorcia, Vincenzo; Giannaccare, Giuseppe (Frontiers in Ophthalmology, 2023)
The aim of this study is to report the clinical outcomes of oral supplementation with curcumin-phospholipid in addition to hyaluronic acid-based tear substitute for the management of dry eye disease (DED). Patients with a diagnosis of DED confirmed by pathological values of both NIKBUT <10 s. and OSDI Questionnaire score > 12 were included. Patients were randomized to receive 2 different treatments: 0.25% hyaluronic acid-based tear substitute 3 time daily (Group 1) or as above plus curcumin-phosphatidylcholine complex tablets once a day (Group 2). Patients were evaluated at baseline (T0) and after 90 days of treatment (T1) by means of Keratograph for the measurement of NIKBUT, TMH, meibomian gland dropout and bulbar redness. Overall, data from 90 eyes of 45 patients were included. Group 1 consisted of 48 eyes of 24 patients, while group 2 included 42 eyes of 21 patients. When comparing median values of both groups at T0, no statistically significant differences were found for all parameters; instead for T1, statistically significant differences were found for redness and OSDI compared to Group 1. In group 1, a statistically significant reduction after the treatment was detected for Nikbut average and OSDI questionnaire; while in group 2, a statistically significant reduction after treatment was recorded for Nikbut average, bulbar redness and OSDI questionnaire. The addition of an oral supplement containing curcumin-phospholipid may help in a greater improvement of bulbar redness and subjective ocular symptoms compared to the treatment with tear substitutes alone for the management of DED.